Can microcystins affect zooplankton structure community in tropical eutrophic reservoirs? - Paes,T. A. S. V. (2016)
Abstract The aim of our study was to assess whether cyanotoxins (microcystins) can affect the composition of the zooplankton community, leading to domination of microzooplankton forms (protozoans and rotifers). Temporal variations in concentrations of microcystins and zooplankton biomass were analyzed in three eutrophic reservoirs in the semi-arid northeast region of Brazil. The concentration of microcystins in water proved to be correlated with the cyanobacterial biovolume, indicating the contributions from colonial forms such as Microcystis in the production of cyanotoxins. At the community level, the total biomass of zooplankton was not correlated with the concentration of microcystin (r2 = 0.00; P > 0.001), but in a population-level analysis, the biomass of rotifers and cladocerans showed a weak positive correlation. Cyclopoid copepods, which are considered to be relatively inefficient in ingesting cyanobacteria, were negatively correlated (r2 = – 0.01; P > 0.01) with the concentration of cyanotoxins. Surprisingly, the biomass of calanoid copepods was positively correlated with the microcystin concentration (r2 = 0.44; P > 0.001). The results indicate that allelopathic control mechanisms (negative effects of microcystin on zooplankton biomass) do not seem to substantially affect the composition of mesozooplankton, which showed a constant and high biomass compared to the microzooplankton (rotifers). These results may be important to better understand the trophic interactions between zooplankton and cyanobacteria and the potential effects of allelopathic compounds on zooplankton.